The diffusion parameters of the extracellular space are altered in focal cortical dysplasias - Vargova, L; Homola, A; Cicanic, M; Kuncova, K; Krsek, P; Marusic, P; Sykova, E; Zamecnik, J (Neuroscience letters, 2011)
Most hypotheses concerning the mechanisms underlying seizure activity in focal cortical dysplasia (FCD) are based on alterations in synaptic transmission and glial dysfunction. However, neurons may also communicate by extrasynaptic transmission, which was recently found to affect epileptiform activity under experimental conditions and which is mediated by the diffusion of neuroactive substances in the extracellular space (ECS). The ECS diffusion parameters were therefore determined using the real-time iontophoretic method in human neocortical tissue samples obtained from surgically treated epileptic patients. The obtained values of the extracellular space volume fraction and tortuosity were then correlated with the histologicaly assessed type of cortical malformation (FCD type I or II). While the extracellular volume remained unchanged (FCD I) or larger (FCD II) than in normal/control tissue, tortuosity was significantly increased in both types of dysplasia, indicating the presence of additional diffusion barriers and compromised diffusion, which might be another factor contributing to the epileptogenicity of FCD.
Keywords: Adolescent; mozková kůra; Adult; Cerebral Cortex; Male; lidé; lidé středního věku; Humans; Child; Malformations of Cortical Development; extracelulární prostor; Middle Aged; malformace mozkové kůry; Young Adult; mužské pohlaví; dospělí; neurony; epilepsie; mladý dospělý; dítě; ženské pohlaví; mladiství; Female; Extracellular Space; Neurons; Epilepsy